Urgensi Konstruksi Hukum Freedom of Speech dan Limitasinya Dalam Rancangan Undang-Undang Kitab Undang-Undang Hukum Pidana - Muchammad Ibnu Shiina Al Musyaawi; Mochammad Rafi Pravidjayanto (Jurist-Diction, 2024)
Abstract There is a need to develop a paradigm in the formation of regulations that protect it freedom of speech as a form of human right in Indonesia in the future and forms the legal construction of the application of restrictions on freedom of speech in a good Criminal Code Bill. So, it doesn't hurt freedom of speech which is part of human rights in Article 28E paragraph (3) of the 1945 Constitution. This research is directed at constructing norms that can be adopted in the Draft Criminal Code regarding criminal acts related to freedom of speech such as pollution, insults, slander and so on. This research uses a juridical-normative method with a conceptual approach to freedom of speech in the Draft Criminal Code and a comparative approach between freedom of speech in Indonesia and the basic rules in the Universal Declaration of Human Rights. The results of this research are in the form of norms that must exist in limiting freedom of speech which can be implemented in the Criminal Code Bill and the development of human rights regulations in Indonesia, especially regarding freedom of speech.   Abstrak Perlunya pengembangan paradigma dalam pembentukan regulasi yang menjaga freedom of speech sebagai salah satu bentuk hak asasi manusia di Indonesia untuk kedepannya, dan membentuk konstruksi hukum penerapan pembatasan freedom of speech dalam RUU KUHP yang baik. Sehingga, tidak mencederai freedom of speech yang merupakan bagian dari hak asasi manusia dalam Pasal 28E ayat (3) Undang-Undang Dasar 1945. Penelitian ini diarahkan untuk mengkontruksi norma yang dapat diadopsi dalam RUU KUHP mengenai tindak pidana yang berhubungan dengan freedom of speech seperti pencemaran, penghinaan, fitnah dan sebagainya. Penelitian ini menggunakan metode yuridis-normatif dengan pendekatan konseptual freedom of speech dalam RUU KUHP dan pendekatan komparatif antara freedom of speech di negara Indonesia dan aturan dasar dalam Deklarasi Universal Hak Asasi Manusia. Hasil penelitan ini berupa norma yang harus ada dalam pembatasan freedom of speech yang dapat diimplementasikan dalam RUU KUHP dan pengembangan regulasi hak asasi manusia di Indonesia terutama mengenai freedom of speech.